Simulation of in-cylinder processes and emission formation in internal combustion engines - Kesgin, U; Safa, A (NORWEGIAN UNIV SCI TECHNOL, 2005)
In order to obtain the effects of design and operational parameters on the engine performance and exhaust gas emissions, i.e. NOx and HC, in-cylinder processes are modeled and evaluated using one-, two- and three zone combustion models for the high pressure part of the engine process and filling and emptying model for the gas exchange part of the engine process. The results are evaluated and compared to the experimental data of a gas engine operating on natural gas displays agreement. The effects of charge pressure and temperature, excess air ratio, start of combustion, combustion duration and form of combustion on the engine performance and on the emissions are investigated and optimum fields of the engine operation regarding engine efficiency and emissions are investigated.
Keywords: emission formation mechanisms; in-cylinder combustion models; engine parameters; Energy & Fuels